THE SYNTHESIS OF SUBSTITUTED ARYL DIAZIRINES - A BIFUNCTIONAL REAGENT SUITABLE FOR APPLICATION TO PHOTOAFFINITY-LABELING STUDIES - Baldwin, J; Jesudason, C; Moloney, M; Morgan, D; Pratt, A (1991)
The 1,3,5-trisubstituted aryl diazirine(2) has been synthesised as a photoaffinity probe and has been elaborated to a reagent suitable for application to studies of penicillin and cephalosporin biosynthetic enzymes. © 1991.